Assessment of potential climate hazard in Switzerland using local climate model - Abt, Kathrin Linda (2023)

(untitled)
Decision makers are increasingly demanding climate information at the national to local scale in order to address the risk posed by projected climate changes and their anticipated impacts. Readily available climate change projections are provided at global and continental spatial scales for the end of the 21st century. However, they do not fit the needs of sub-national adaptation planning that requires regional or local projections. To fill in these gaps, this study aims to provide reliable information by developing a Regional Climate Model (RCM) for Switzerland using the Statistically Downscaling Method. The objectives of the study are to: 1) develop the RCM based on precipitation and temperature data, 2) assess the reliability of the RCM based on different SSP scenarios using Linear Regression, Cronbach‘s Alpha, and Probability Density Function, and 3) assess potential climate hazard based on the RCM created and recommend the most suitable SSP scenario for future climate change projection in Switzerland. The result shows that SSP4.5 is the most suitable scenario for future climate projections in Switzerland. The generated RCM provides critical information to support Swiss government, policy makers, and society in developing effective adaptation strategies for climate change. The impacts of increasing temperatures in Switzerland will likely include melting of glaciers and snowpack, leading to changes in water availability for agriculture and drinking water, and increased risk of flash floods and landslides. Further, there will be an increased risk of heatwaves and associated health impacts, and changes in tourism and recreational opportunities. The study contributes to the ongoing efforts to understand and address the complex challenges of climate change